Mechanical behavior of nanocrystalline metals and alloys - Kumar, K.S; Van Swygenhoven, H; Suresh, S (Acta materialia, 2003)
Nanocrystalline metals and alloys, with average and range of grain sizes typically smaller than 100 nm, have been the subject of considerable research in recent years. Such interest has been spurred by progress in the processing of materials and by advances in computational materials science. It has also been kindled by the recognition that these materials possess some appealing mechanical properties, such as high strength, increased resistance to tribological and environmentally-assisted damage, increasing strength and/or ductility with increasing strain rate, and potential for enhanced superplastic deformation at lower temperatures and faster strain rates. From a scientific standpoint, advances in nanomechanical probes capable of measuring forces and displacements at resolutions of fractions of a picoNewton and nanometer, respectively, and developments in structural characterization have provided unprecedented opportunities to probe the mechanisms underlying mechanical response. In this paper, we present an overview of the mechanical properties of nanocrystalline metals and alloys with the objective of assessing recent advances in the experimental and computational studies of deformation, damage evolution, fracture and fatigue, and highlighting opportunities for further research.